THE EFFECT OF USING THE GEOGEBRA APPLICATION-ASSISTED DISCOVERY LEARNING MODEL ON LEARNING OUTCOMES - Maya Sari, Chintya; Bustanul Anwar, Rahmad; Vahlia, Ira (EMTEKA: Jurnal Pendidikan Matematika, 2025)
The purpose of this study is to evaluate the effectiveness of the Geogebra app in facilitating the discovery learning paradigm in mathematics instruction for junior high school pupils. The experimental technique is used for the investigation. Using Simple Random Sampling, 17 students from the eighth grade boys' class and 20 students from the eighth grade girls' class served as the experimental and control groups, respectively. The assessment tool used is an essay-based exam. Observation, interviews, documentation, and testing are all methods of data gathering, and a t-test is used for data analysis. The study found that compared to traditional learning models, the discovery learning model with the use of the Geogebra app had an effect size of 2.143>2.030, indicating a relationship between the two. This is due to the fact that students are motivated to actively participate in problem-solving via the exploration of their own talents, investigation of the issue, and eventual solution, all of which are supported by the discovery learning paradigm and made possible by the Geogebra program. It follows that Geogebra's discovery learning methodology affects Sunan Ampel Punggur Middle School students' performance in the classroom